Reported Barriers Impeding Adherence to a Physical Exercise Program in Patients With Breast Cancer: A Systematic Review. Issue 2 (April 2021) - Michael, Meghan; Goble, Jordan; Hawk, Megan; Kujawa, David J.
Abstract : Background: More than 80% of those newly diagnosed with breast cancer are now surviving 5 years or more, which creates a target group that is in need of activity programs to prevent treatment side effects and complications. Purpose: The purpose of our systematic review was to identify patient perceptions, preferences, and barriers as well as the strategies to improve adherence to a physical exercise program. Data Sources: PubMed, Academic Search Complete, MEDLINE, SPORTDiscus, EMBASE, Web of Science, PsycINFO, and CINAHL were searched, yielding 2511 studies. Study Selection: In total, 16 qualitative studies were retained and published from 2013 to 2018 in English. Data Extraction: Three reviewers independently extracted data from the studies, evaluated the evidence, and organized the data into tables for ease of reference and analysis. Data Synthesis: Of the 16 retained studies, 7 used interviews, 6 used surveys/questionnaires, and 3 used a mix of interviews and questionnaires. The CASP (Critical Appraisal Skills Programme) instrument was used to appraise quality. Discussion and Limitations: Patient education, group-based programming, electronic tracking devices, enhancing confidence and self-efficacy, and providing alternatives for exercising at home were identified as strategies that could be used to improve adherence. Publication bias and 100% female participation within the retained studies could have affected the results of this review. Conclusions: The barriers, perceptions, preferences, motivators, and recommendations that have been identified will enable physical therapists to optimize, design, and implement a well-rounded program for the initiation and maintenance of physical activity for women with breast cancer. Abstract : Supplemental Digital Content is Available in the Text.